Language and the body in the performance reception of Senecan tragedy - Slaney, H (2013)
Seneca’s contribution to the development of Western European theatre and conceptions of theatricality has been underestimated in comparison to that of Greek tragedy. This thesis argues for the continuous importance of Senecan drama in theatrical theory and practice from the sixteenth century until the present day. It examines significant instances of Seneca in performance, and shows how these draw on particular aspects of Seneca’s style and dramaturgical technique to coalesce into a sub-genre of tragedy termed here ‘hypertragedy’ or the ‘senecan aesthetic’. The underlying premise of this representational mode is that verbal (vocal) performance is a physical act and induces physical responses. This entails the consequential inference that Senecan theatre is not mimetic – that is, based on an isomorphic identification of character with performer – but rather affective; like oratory, it functions through direct, quasi-musical manipulation of the auditor’s senses. The goal of this theatrical form is to articulate extreme states of mind or experiences which cannot be conveyed via conventional mimetic means: pain, frenzy, dissolution of the self. In tracing the theories of tragedy which comprise a narrative contrapuntal to the reception of Seneca onstage, it is possible to identify the factors which have successively constructed, promoted, suppressed, reviled and finally reinstated the senecan aesthetic as philhellenism’s other.